Enhancing Logistics Performance through Digital Marketing Capabilities: Examining Customer Engagement and Supply Chain Integration - Shwawreh, Sally; Ali, Ahmad; Taroum , Alauldin S. A.; Al-Shaikh, Mustafa S. (International Review of Management and Marketing, 2026)
The study considers the influence of the digital marketing capabilities on logistics performance using customer engagement as a mediating variable and digital supply chain integration as the moderating variable. Based on the resource-based view and dynamic capabilities theory, the study starts with the proposition that digital marketing capabilities allow firms to leverage the digital platforms, customer data, digital analytics, and online communication to enhance customer interaction and logistics related outcomes. A quantitative research design was used and data was gathered using a structured questionnaire from the employees and managers in logistics related firms such as logistics service providers, delivery firms, transportation firms, third party logistics providers and e-commerce logistics firms. Structural Equation Modeling was used to analyze the data. Results indicated a positive relationship between digital marketing capabilities and logistics performance and customer engagement. Results further indicated that customer engagement has a positive impact on logistics performance and partially mediated the digital marketing capabilities–logistics performance relationship. Furthermore, it was observed that digital supply chain integration contributes to reinforce the links between digital marketing capabilities and logistics performance. The results in this research add to the literature by connecting the digital marketing capabilities with the logistics performance and by explaining the effect of customer engagement and digital supply chain integration in this relationship.